Peran Otoritas Keagamaan dalam Penetapan 1 Syawal di Indonesia dan Thailand Serta Implikasi Sosialnya - Iskandar, Mohammad Fajar; Nugroho, Machrus Hakim; Laehka, Aree (Program Studi Ilmu Falak UIN Sunan Ampel Surabaya, 2024)
This study discusses a comparison of the determination of 1 Shawwal in Thailand and Indonesia, focusing on the methodology used, the role of religious authorities, and the social implications that arise. This research is a literature review with a qualitative approach. Data was collected through literary studies and documentation, then the data was analyzed in a comparative descriptive manner. The results of the study show that although the rukyat and hisab methods are used in both countries, the implementation is different. In Indonesia, the decision to determine 1 Shawwal is carried out through an isbat session involving various Islamic organizations, while in Thailand, the Sheikhul Islam Office has full authority in the determination. These differences affect social dynamics, with Indonesia experiencing differences in celebration times between mass organizations, while in Thailand, centralized decisions result in uniformity. These findings provide insight into how the methodology and structure of religious authority affect the religious practices and social relations of Muslims in both countries